Renewable Energy Contribution Based on Microgrid Using Photovoltaic and Wind Turbine Scenario - Handoko Rusiana Iskandar; Yusuf Irwin Deriantono; Dede Furqon; Naftalin Winanti (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Indonesia's renewable energy mix offers an alternative to conventional fossil fuels. Indonesia has made a significant commitment to the role of exploiting this new energy in accordance with the Paris Agreement. This paper proposes the design of a microgrid architecture for a solar and wind hybrid power plant with grid-connected configuration and micro-scale power plant modeling in Ciheras Village, Cipatujah District, Tasikmalaya Regency, West Java. This architecture is divided into three scenarios in order to determine the best design qualities. The first scenario involves 50% photovoltaic (PV) and 50% wind turbine (WT), the second 60% PV and 40% WT, and the third 70% PV and 30% WT. The findings of the grid-connected microgrid were compared using supporting software, HOMER Pro. The various scenarios yielded performance analysis and renewable energy contribution. Modeling, calculation, simulation, and analysis demonstrate that the first scenario's potential energy output produces 25,655 kWh/year with an 88.2% Renewable Fraction (RF). The second scenario generates 26,194 kWh of energy per year, with a renewable fraction of 87.8%. The third scenario is the best based on the participation and role of distributed energy (PV-WT), with a higher amount of energy output of 30,691 kWh/year and a higher renewable proportion of 89%.